Functional performance training DVD [ - Liebenson, Craig (Lippincott Williams & Wilkins, 2011)
Perfect for individuals of all ages and fitness levels, the Functional Performance Training DVD is the key to restoring function and maintaining an active lifestyle. Through activity and sport-specific training, this DVD helps to train balance, agility, and power for your whole body. Functional training involves the same movements you use in your daily life. This DVD emphasizes movement patterns which are important for daily tasks and sport or recreational activities. In contrast to traditional strength training which isolates individual muscles, Dr. Liebenson guides you in functionally integrated patterns that you will use in pushing, pulling, lifting, or carrying activities. This DVD will help you gain a basic movement literacy in the fundamental A.B.C.'s of agility, balance, and coordination